2018
DOI: 10.1155/2018/1879329
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Methamphetamine Abuse: A Rare Case of Rapid Cerebral Aneurysm Growth with Review of Literature

Abstract: Methamphetamine or “meth” is a sympathomimetic amine of the amphetamine-type substances (ATS) class with an extremely high potential for abuse. Illicitly abused neurostimulants like cocaine and meth predispose patients to the aneurysmal formation with reported rupture at a younger age and in much smaller sized aneurysms. However, very rapid growth of aneurysm within less than 2 weeks with methamphetamine abuse is very rarely observed or reported. In this report, we present a patient with repeated and recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In addition to hypertension, a direct effect of methamphetamine and related molecules such as beta-aminopropionitrile on the vasculature has been characterized, including a necrotizing angiitis, 26,27 neurovascular inflammation and weakening of vessel walls via matrix metalloproteases and inflammatory cytokines. 2830 Also, rapid growth of intracranial aneurysms after methamphetamine abuse 28 , 31 has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hypertension, a direct effect of methamphetamine and related molecules such as beta-aminopropionitrile on the vasculature has been characterized, including a necrotizing angiitis, 26,27 neurovascular inflammation and weakening of vessel walls via matrix metalloproteases and inflammatory cytokines. 2830 Also, rapid growth of intracranial aneurysms after methamphetamine abuse 28 , 31 has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, posterior circulation aneurysms were noted in 21 (20%) of patients in the MA absent cohort, with three (14.3%) having vasospasm exclusively involving the posterior circulation and 12 (57.1%) with both posterior and anterior circulation vasospasm. Use of MA has been linked with increased risk of aneurysm formation as well as accelerated growth, abnormal morphological changes and rupture, likely owing to direct toxic effects on the vasculature leading to in ammation and impaired vessel wall integrity (17,39,40). Although multiple prior studies did not nd an interaction between MA use and aneurysm location, a recently published large case series of MA related aneurysms found that while anterior circulation aneurysms were more common overall (77%), posterior aneurysms were disproportionately more likely to present with rupture compared to anterior aneurysms (65% vs 32%) and rupture despite smaller size (8, [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the patient may have experienced a rare sudden enlargement of the aneurysm after the second onset of symptoms, as previously described by Miller et al [ 11 ] and Khan et al [ 12 ]. Previous reports of the rapid growth of cystic aneurysms show that this condition often occurs in patients with atrial myxoma, inflammatory aneurysms, drug abuse, and blood vesicular aneurysms[ 13 - 16 ], and its causes have been reported to be related to pregnancy, surgery, hypertension, and sex[ 17 , 18 ]. However, all of the aforementioned factors were excluded based on the patient’s medical history, except a suspicious history of trauma.…”
Section: Discussionmentioning
confidence: 99%